2021
DOI: 10.3389/fnano.2021.782883
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited Platinum Iridium Enables Microstimulation With Carbon Fiber Electrodes

Abstract: Ultrasmall microelectrode arrays have the potential to improve the spatial resolution of microstimulation. Carbon fiber (CF) microelectrodes with cross-sections of less than 8 μm have been demonstrated to penetrate cortical tissue and evoke minimal scarring in chronic implant tests. In this study, we investigate the stability and performance of neural stimulation electrodes comprised of electrodeposited platinum-iridium (PtIr) on carbon fibers. We conducted pulse testing and characterized charge injection in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…5 b). A percentage of 59% for Pt and 41% of Ir was measured on one electrode, comparable with previous results 43 . SEM was done after electrodeposition but prior to hydrogel coating.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…5 b). A percentage of 59% for Pt and 41% of Ir was measured on one electrode, comparable with previous results 43 . SEM was done after electrodeposition but prior to hydrogel coating.…”
Section: Resultssupporting
confidence: 91%
“…Electrical performance of the FFA was significantly improved by Pt/Ir electrodeposition and most of this improvement was maintained despite coating the electrodes with hydrogel. We found that contaminations from SEM and residual PDMS caused a variation of both impedance and CSC C of the naïve electrodes, but electrodeposition effectively cleaned the electrode surface and improved the electrical properties of the electrodes due to the properties of the Pt/Ir alloy 43 . After electrodeposition, the standard deviation of the impedance at 1 kHz was reduced to 5.53%.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Carbon fibers were then plasma ashed in a Glen 1000P Plasma Cleaner (Glen Technologies Inc., Fremont, CA). Fiber tips were functionalized in one of two ways: 1) electrodeposition by dipping carbon fibers in a solution of 0.01 M 3,4-ethylenedioxythiophene (483028, MilliporeSigma, Darmstadt, Germany) and 0.1 M sodium p-toluenesulfonate (152536, MilliporeSigma) and applying 600 pA/channel using a PGSTAT12 potentiostat (EcoChemie, Utrecht, Netherlands) to coat the tips with PEDOT:pTS 25,61 (N=3 arrays) or 2) electrodeposition of Platinum Iridium (PtIr) with a Gamry 600+ potentiostat (Gamry Instruments, Warminster, PA) (N=2 arrays) using previously published methods 89 .Silver ground and reference wires (AGT05100, World Precision Instruments, Sarasota, FL) were soldered to the PCB, completing assembly. For one electrode, a support tine was broken off prior to implant as a sham channel for a separate study (for rat #1).…”
Section: Methodsmentioning
confidence: 99%